Reasons and evolution of non-thrombolysis in acute ischaemic stroke. Issue 4 (25th October 2016) - Reiff, T; Michel, P
Abstract : Introduction: Despite increasing evidence of its efficacy in advanced age or in mild or severe strokes, intravenous thrombolysis remains underused for acute ischaemic stroke (AIS). Our aim was to obtain an updated view of reasons for non-thrombolysis and to identify its changing patterns over time. Methods: This is a retrospective study of prospectively collected data from the Acute Stroke Registry and Analysis of Lausanne (ASTRAL) from the years 2003–2011. Patients admitted with acute stroke in the past 24 hours who had not had thrombolysis were identified; reasons for non-thrombolysis documented in the prospectively entered data were tabulated and analysed for the group as a whole. Data were analysed for the years 2003–2006 and 2007 forward because of changes in contraindications. A subgroup of patients who arrived within the treatment window ≤180 min was separately analysed for reasons for non-thrombolysis. Predictors of non-thrombolysis were investigated via multivariate regression analyses. Results: In the 2019 non-thrombolysed patients the most frequent reasons for non-thrombolysis were admission delays (66.3%), stroke severity (mostly mild) (47.9%) and advanced age (14.1%); 55.9% had more than one exclusion criterion. Among patients arriving ≤180 min after onset, the main reasons were stroke severity and advanced age. After 2006, significantly fewer patients were excluded because of age (OR 2.65, p<0.001) or (mostly mild) stroke severity (OR 10.56, p=0.029). Retrospectively, 18.7% of all non-thrombolysed patients could have been treated because they only had relative contraindications. Conclusion: Onset-to-admission delays remain the main exclusion criterion for thrombolysis. Among early arrivals, relative contraindications such as minor stroke severity and advanced age were frequent. Thrombolysis rate increased with the reduction of thrombolysis restrictions (eg, age and stroke severity).